Co-pyrolysis of microwave-assisted acid pretreated bamboo sawdust and soapstock. (October 2018) - Wang, Yunpu; Wu, Qiuhao; Duan, Dengle; Zhang, Yayun; Ruan, Roger; Liu, Yuhuan; Fu, Guiming; Zhang, Shumei; Zhao, Yunfeng; Dai, Leilei; Fan, Liangliang
Highlights: Pretreated bamboo and soapstock were co-pyrolysis into bio-oil. The microwave irradiation was the sole heating method in whole process. The oxygenates and biochar decreased dramatically in bio-oil. The maximum relative content of gasoline (73.30%) was achieved. Abstract: Fast microwave-assisted co-pyrolysis of pretreated bamboo sawdust and soapstock was conducted. The pretreatment process was carried out under microwave irradiation. The effects of microwave irradiation temperature, irradiation time, and concentration of hydrochloric acid on product distribution from co-pyrolysis and the relative contents of the major components in bio-oil were investigated. A maximum bio-oil yield of 40.00 wt.% was obtained at 200 °C for 60 min with 0.5 M hydrochloric acid. As pretreatment temperature, reaction time and acid concentration increased, respectively, the relative contents of phenols, diesel fraction (C12 + aliphatics), and other oxygenates decreased. The gasoline fraction (including C5–C12 aliphatics and aromatics) ranged from 55.77% to 73.30% under various pretreatment conditions. Therefore, excessive reaction time and concentration of acid are not beneficial to upgrading bio-oil.